Dekonstruksi dalam Novel Ranah 3 Warna Karya Ahmad Fuadi - Marzuq, Ahmad; ., Zuriyati; Gomo Attas, Siti (Humanis, 2021)
This study aims to find other meanings for the novel Ranah 3 Warna. Researchers use deconstruction theory to uncover and see the other side of the character Alif who is described as a character who is persistent, tough and unyielding. This research uses literature study method to collect and provide data to be analyzed. The data source in this research is the text of the novel Ranah 3 Warna by Ahmad Fuadi, first printed in January 2011 by PT Gramedia Jakarta. The data was collected by using the method of reading repeatedly carefully against the manuscripts that were the object of the research. The data analysis used in this research is descriptive analysis technique by describing the data which is then followed by the analysis. Based on the text analysis and other meanings carried out on the novel Ranah 3 Warna, it is revealed the figures of people who have had a big influence in Alif's life. Among them, Kyai Rais, Ayah, Bang Togar and Randai. Other analysis results reveal that Alif is easily offended, is less grateful and forgets the services of his little friend Randai who has sacrificed a lot for his survival overseas. In addition, Alif also has a character that does not accept reality and is ambitious in achieving what he wants.